(untitled) (SCIÉNDO INGENIUM, 2025)
Pitahaya pulp contains a high proportion of antioxidant components. The traditional methods and thermal treatments used in fruit processing alter the phytochemical and nutraceutical constituents and restrict the use of its benefits, therefore, we examined an innovative and relevant technique that allows the preservation of its constituents, converging that, to achieve our objective, the submersion in ultrasound pulping contributes to the preservation of the antioxidant properties of pitahaya. In our experimental investigation, pitahaya pulp was separated, sectioned into slices and frozen at -48 °C, freeze-dried for about 48 hours, the dry sample was ground and macerated for 7 days in pure methyl alcohol, dividing the extract into different fractions to measure the antioxidant potential through the DPPH method with the help of a spectrophotometer. The antioxidant capacity was calculated directly in a portion of the filtered sample without sonication; to other similar fractions, ultrasound baths were applied prior to their disquisition in the spectrophotometer, determining that, applying 20 minutes of ultrasound, 40 kHz frequency and 250 W of power, is the most convenient to preserve the antioxidant capacity of the pitahaya pulp.